Effects of whey on the quality and microbial diversity of pickled radish - WANG Xinrui, LI Hong, TANG Rong, MA Yiran, CHEN Junfei, TANG Huihua, LIU Biqin, LI Huimin, SHI Qiao (Zhongguo niangzao, 2025)
In order to explore the effect of whey on the quality and microbial community diversity of pickled radish, radishes were soaked in salt water, unfermented whey and naturally fermented whey (numbered as C, N and F, respectively), the pH, total acid, nitrite contents and brittleness changes of pickled radish during the fermentation process were determined, and the microbial community diversity of samples N and F was analyzed by high- throughput sequencing technology. The results showed that the quality of sample F was good. At 6 h of fermentation, the pH was less than 4, the total acid content reached 1.5%, the brittleness was 28 N, and the nitrite content during the fermentation process was less than 4 mg/kg. The microbial diversity analysis indicated that the absolute dominant bacterial genera and species during the fermentation process of sample F were Lactobacillus and Lactobacillus helveticus (relative abundance>95%), respectively. The dominant fungal genera were Pichia, Candida, Trichosporon, etc. (relative abundance all>1%), and the dominant fungal species were Pichia kudriavzevii (relative abundance>40%). Naturally fermented whey could stabilize the microbial community structure of pickled radish, shorten the fermentation cycle, and produce a positive impact on its quality.